MOLECULAR IDENTIFICATION AND CLONAL RELATION OF ATYPICAL ISOLATE Aeromonas salmonicida USING RESTRICTION FRAGMENT LENGTH POLYMORPHISM (RFLP) - Riza Priyatna; Indaryulianto Indaryulianto; Kurniasih Kurniasih (Indonesian Aquaculture Journal, 2011)
Aeromonas salmonicida is responsible in many cases of furunculosis outbreaks resulting in economic loss of freshwater aquaculture. Four isolates of A. salmonicida have been isolated from fish collected in four different regions in Indonesia and its clonal relation has yet to be determined. In the research, A. salmonicida isolates and ATCC atypical isolate as the control had been checked for their clonal relation using Restriction Fragment Length Polymorphism (RFLP) method in which restriction enzyme of AluI, HaeIII, MboI, and EheI were used. PCR test results using the primers 16S rDNA amplicon gave a positive response to the 1300 bp band. The result of RFLP analysis showed that A. salmonicida atypical isolates from Indonesia represent subspecies smithia except isolates from C. macropomum in Yogyakarta in MS and 16S rDNA regions. Isolates from Jambi, Pontianak and Semarang showed a slight variation on enzyme restriction sites. Isolates number 2, 3, 4 and 5 had the same restriction sites using AluI enzyme with MS primer. The restriction enzymes that could give the best result for RFLP method of A. salmonicida were HaeIII, MboI and EheI.